2022
DOI: 10.1161/atvbaha.122.317676
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell TGF-β (Transforming Growth Factor-Beta) Signaling Regulates Venous Adaptive Remodeling to Improve Arteriovenous Fistula Patency

Abstract: BACKGROUND: Arteriovenous fistulae (AVF) are the gold standard for vascular access for hemodialysis. Although the vein must thicken and dilate for successful hemodialysis, excessive wall thickness leads to stenosis causing AVF failure. Since TGF-β (transforming growth factor-beta) regulates ECM (extracellular matrix) deposition and smooth muscle cell (SMC) proliferation—critical components of wall thickness—we hypothesized that disruption of TGF-β signaling prevents excessive wall thickening during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…TGF-β, BMP, and insulin growth factor are all associated with AVF stenosis (23, 51-53). TGF-β in particular plays an important role in AVF vascular remodeling, regulating ECM deposition and VSMC proliferation (54,55). Gdf10, Tgfb3, and Igf2 were strongly downregulated with BAPN treatment along with TGF-β and insulin growth factor ECM binding proteins, Ltbp3, Ltbp4 and Igfbp5.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β, BMP, and insulin growth factor are all associated with AVF stenosis (23, 51-53). TGF-β in particular plays an important role in AVF vascular remodeling, regulating ECM deposition and VSMC proliferation (54,55). Gdf10, Tgfb3, and Igf2 were strongly downregulated with BAPN treatment along with TGF-β and insulin growth factor ECM binding proteins, Ltbp3, Ltbp4 and Igfbp5.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β, a multifunctional cytokine, exerts control over extracellular matrix (ECM) deposition and SMC proliferation, both of which hold pivotal roles in neointimal hyperplasia leading to AVF stenosis [ 42 , 43 , 57–64 ]. Elevated TGF-β expression within stenoses in human AVF [ 43 ], and genetic polymorphisms that express high amounts of TGF-β protein correlate with lower AVF patency [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β assumes a central role in kidney and vascular fibrosis and stands as a determinant for AVF functioning [ 67 ]. Additionally, TGF-β orchestrates inflammation within the remodeling AVF wall [ 42 ]. The pivotal role of inflammation in vascular remodeling and AVF maturation, with macrophages playing an essential part in AVF maturation, underscores the significance of inflammatory cells [ 68–71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Arteriosclerosis, Thrombosis, and Vascular Biology , Taniguchi et al 1 report that targeting the TGFBR (TGFβ [transforming growth factor β] receptor) can improve AVF patency. This study disrupted the TGFβ pathway by a pharmacological agent, and by genetic cell specific deletion of TGFβ receptor in smooth muscle cells (SMCs, Tgfbr2 flx/flx / Myh11-CreER T2 ) or endothelial cells (ECs, Tgfbr1/2 flx/flx /Cdh5-CreER T2 ; Figure).…”
mentioning
confidence: 99%
“…Taniguchi et al 1 identified the ECs as the key cell type in regulating venous remodeling in the AVF. Using a similar mouse AVF model, an earlier study reported that AVF formation resulted in a significant increase in the blood pressure in the vein due to its exposure to the aortic flow.…”
mentioning
confidence: 99%